Engaging street‐involved youth using an evidence‐based intervention: A preliminary report of findings. Issue 2 (28th September 2017) - Lynch, Joanna; McCay, Elizabeth; Aiello, Andria; Donald, Faith
Abstract: Problem: Street‐involved youth experience many barriers to accessing health and social services. There is a literature gap in the literature regarding evidence‐based interventions to facilitate engagement with street‐involved youth. Methods: A qualitative descriptive study of preliminary findings from a large mixed‐methods study was undertaken to assess the impact of a resilience‐based motivational intervention. This intervention was grounded in frameworks including strengths‐based and resilience‐based communication using the Seven C's Model of Resilience, positive youth development, and motivational interviewing that are particularly relevant to youth. Individual interviews were conducted with two subsets of youth who participated ( n = 3) or did not participate ( n = 3) in the intervention. Thematic analysis was conducted to identify themes between the intervention and comparison groups. Findings: Preliminary themes identified across the sample include (1) establishing a trusting relationship, (2) strengthening self‐worth and resilience, (3) focusing on goals, and (4) perceiving a sense of hope and possibility . Conclusions: The themes identified the importance of positive relationships with care providers built upon a foundation of trust to engage youth to remain motivated and focused on their goals.